O símbolo e a crença: a centralidade simbólica nos sistemas religiosos do judaísmo e cristianismo: história, significação e atualidade - Ferrentini, Mara Liz Hernandes (2007)
First of all, this research is focused on an approximate and panoramic way of religious symbols of the ancient religions, providing explanation to understanding these religions at the first periods of humanity. Following, this research focused on the symbolical universe of Jewish and Christian systems. This search is talking about basic symbolism on both Judaism and Christians traditions, as well as investigating their symbolical evolution by anthropological and philosophical references. At last, this research showed the presence of Judaism in Christian culture, giving it its notorious autonomy, but with clearly Jewish foundations.